Develop a Prototype of a Bangkok Floating Market Attraction Simulation Game Using Gamification - Wantayakul, Nathayu; Tirastitam, Pimploi; Whangmahaporn, Benya; Kerdpitak, Napassorn; Sirikamonsin, Patsara; Waiyawuththanapoom, Phutthiwat (Journal of Ecohumanism, 2025)
Background. The emerging trend of gamification and its potential to enrich experiential growth and promotional efforts in the tourism industry. Gamification, an emerging field of study, symbolizes a rising trend with various uses in tourism, intending to foster motivation and induce behavioral changes. Objective. design prototypes with gamification concepts Methods. the qualitative research method includes In-depth interviews with the key informant all total 14 people. The purposive sampling was uses in the research study. Result. These aspects capture of the design prototypes with gamification concepts which consisting of (1) Expectations (2) The game prototypes can provide valuable insights into their behavior (3) Usability issues (4) Identify usability challenges (5) Decision-making strategies. Those elements involved in user interaction with the game prototypes of "The Bangkok Travel Floating Market" gamification. Conclusion. Designing to be contemporary and aligned with the behaviors and preferences of the target audience can captivate players by offering rewards and creating challenges, as well as fostering social interaction within the gaming community. It can also stimulate cultural awareness to promote inspiration for cultural tourism in the significant Bangkok floating market attraction.